Popular knowledge about medicinal plants in rural communities in the municipality of Laranjeiras do Sul, Parana, Brazil - Glowka, Karen Karoline de Oliveira (2021)
This research aimed to rescue popular knowledge about medicinal plants used to promote health and agroecology in the municipality of Laranjeiras do Sul - Paraná. An ethnobotanical study with a quantitative approach was carried out, following the descriptive method, from a field research with farmers from the communities of Passo Liso, Rio do Tigre and Rio Verde, located in this municipality, between the months of November 2018 to January 2019 , through pre-scheduled visits and accompanied by the Community Health Agent (CHA) of the respective community. The data were obtained with sixteen families in the community of Passo Liso, nineteen families in the community Rio Verde and fifteen families in the community Rio do Tigre, totaling 50 families of farmers, randomly indicated by the ACS of the micro area corresponding to the Health Unit of SUS. The results showed that 100% of farmers use medicinal plants to treat disease symptoms, and have these plants in their backyards. Were 73 species cited, of which the five plants most used by farmers are: Mentha spp. (mint), Rosmarinus officinalis L. (rosemary), (Zingiber officinale Rosc.) ginger, Artemisia absinthium L. (worm) e Chamomilla recutita (L.) (chamomile).